2021
DOI: 10.1039/d0fd00080a
|View full text |Cite
|
Sign up to set email alerts
|

Using highly time-resolved online mass spectrometry to examine biogenic and anthropogenic contributions to organic aerosol in Beijing

Abstract: We study the anthropogenic and biogenic contributions to organic aerosol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 123 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…One possible explanation was the different formation mechanisms of LO-OOA in summer and winter. Although LO-OOA was dominantly from oxidation of anthropogenic VOCs, for example, organic nitrates from NO 3 oxidation at nighttime in winter due to low emissions of biogenic VOCs, it could have a large contribution from oxidation of biogenic VOCs in summer . Indeed, previous studies found that the monoterpene- and sesquiterpene-derived SOA decreased and the anthropogenic SOA from toluene oxidation increased with the increase in the height in the city …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation was the different formation mechanisms of LO-OOA in summer and winter. Although LO-OOA was dominantly from oxidation of anthropogenic VOCs, for example, organic nitrates from NO 3 oxidation at nighttime in winter due to low emissions of biogenic VOCs, it could have a large contribution from oxidation of biogenic VOCs in summer . Indeed, previous studies found that the monoterpene- and sesquiterpene-derived SOA decreased and the anthropogenic SOA from toluene oxidation increased with the increase in the height in the city …”
Section: Resultsmentioning
confidence: 99%
“…Although LO-OOA was dominantly from oxidation of anthropogenic VOCs, for example, organic nitrates from NO 3 oxidation at nighttime 58 in winter due to low emissions of biogenic VOCs, it could have a large contribution from oxidation of biogenic VOCs in summer. 59 Indeed, previous studies found that the monoterpene-and sesquiterpene-derived SOA decreased and the anthropogenic SOA from toluene oxidation increased with the increase in the height in the city. 43 We further compared the vertical differences between daytime and nighttime that were defined according to the diurnal variations of MLH (Figure S9).…”
Section: Aerosol Composition In the Urban Boundarymentioning
confidence: 98%
“…These I – -adduct ions (C x H y O z X n , where X = S or N, x , y , z ≥ 1 and n ≤ 2) contributed to 90–97% of the total signals of the detected organic ions, which consist of 989 C x H y O z , 856 C x H y O z N n , and 36 C x H y O z S n I – -adduct ions. In the C x H y O z N n category, 583 compounds with the formula of C x H y O z N 1 ( y is an odd number ≤ 2 x + 3 and z ≥ 4 except C 6 H 5 NO 4 , C 7 H 7 NO 4 , and C 8 H 9 NO 4 that were more likely nitrated phenols in urban environments) were tentatively designated as ONs. Signal contributions of ions with two nitrogen or sulfur atoms are relatively minor. We also fitted three deprotonated organosulfate ions (i.e., C 3 H 5 SO 5 – , C 2 H 3 SO 6 – , C 3 H 5 SO 6 – ) in the analysis.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…POs are also frequently detected in ambient particles. ,,,, Particulate POs have been measured as HOMs using offline filter analysis by LC-ESI-MS. ,,, In recent years, online analytical techniques such as FIGAERO-ToF-CIMS , and EESI-ToF-MS ,, have been applied to characterize POs in ambient particles. Oxygenated organic compounds in the particle phase measured by FIGAERO-ToF-CIMS explained 24% of the total organic aerosol mass measured by AMS at an urban site during the autumn season in Guangzhou, among which substantial species could be POs .…”
Section: Observations Of Pos In Laboratory and Field Studiesmentioning
confidence: 99%
“…Oxygenated organic compounds in the particle phase measured by FIGAERO-ToF-CIMS explained 24% of the total organic aerosol mass measured by AMS at an urban site during the autumn season in Guangzhou, among which substantial species could be POs . Source apportionment analyses, like positive matrix factorization (PMF) and clustering analysis of MS data derived from online measurements, have helped reveal the major sources of particulate HOMs and their temporal evolution in different atmospheric environments. ,, The enrichment of HOMs in ambient particles may be relevant to the activation of cloud condensation nuclei (CCN). ,, Organic aerosol with higher oxygenation level was observed to have higher CCN activity. , In boreal regions, monoterpene-derived HOMs could result in an overall 10% enhancement in CCN concentration . There may also be implications on potential health impacts of PM that is rich in HOMs.…”
Section: Observations Of Pos In Laboratory and Field Studiesmentioning
confidence: 99%